2018
DOI: 10.15583/jpchrom.2018.016
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Behavior in Nonaqueous Capillary Zone Electrophoresis Using Tetrahydrofuran-Based Ternary Nonaqueous Solutions

Abstract: Nonaqueous capillary electrophoresis has the potential to separate water-insoluble analytes. Previously, we reported the separation of water-insoluble and neutral synthetic polymers in nonaqueous capillary zone electrophoresis using tetrahydrofuran (THF)-based ternary nonaqueous solutions. In this paper, the effect of the composition of a THF-based ternary solution (THF, acetonitrile, and methanol) containing cetyltrimethylammonium chloride (CTAC) on electrophoretic behavior is investigated using small organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In our previous study with THF-based electrophoretic media, we found that small compounds without high hydrophobicity was not interact with the cetyltrimethylammonium (CTA) cation [15]. In this study, as the neutral marker soluble in HFIP, phenol was employed as EOF marker which less interacts with CTA cation in HFIP.…”
Section: Electroosmotic Flow In Hfip Containing Ctacmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous study with THF-based electrophoretic media, we found that small compounds without high hydrophobicity was not interact with the cetyltrimethylammonium (CTA) cation [15]. In this study, as the neutral marker soluble in HFIP, phenol was employed as EOF marker which less interacts with CTA cation in HFIP.…”
Section: Electroosmotic Flow In Hfip Containing Ctacmentioning
confidence: 92%
“…In subsequent studies, we investigated the effect of surfactant species and electrophoretic medium compositions on electrophoretic behaviors using THF-based electrophoretic media [13][14][15]. Specifically, synthetic polymers soluble in THF were used as test analytes for these investigations.…”
Section: Introductionmentioning
confidence: 99%
“…In the aforementioned studies, THF-soluble polymers were used as test analytes. Therefore, tetrahydrofuran-based ternary nonaqueous solutions were used for the investigation [57]. However, there are many linear polymers insoluble in THF-based solutions.…”
Section: Tablementioning
confidence: 99%
“…Uchida et al reported on the effect of the composition of a THF-based ternary solution containing CTAC on the electrophoretic behavior of small organic compounds. 6 They found that the THF content has an important role in the electrophoretic behavior in NACE. The same research group also reported on an evaluation of interactions between the anionic complex of palladium(II) and the extraction reagent in the presence of SDS or polyoxyethylene alkylphenyl ether by CE, demonstrating that the Pd complex is rapidly captured by the polyoxyethylene micelles compared with the SDS micelles.…”
mentioning
confidence: 99%